2019
DOI: 10.3389/fphar.2019.00015
|View full text |Cite
|
Sign up to set email alerts
|

Potential Novel Prediction of TMJ-OA: MiR-140-5p Regulates Inflammation Through Smad/TGF-β Signaling

Abstract: Temporomandibular joint osteoarthritis (TMJ-OA), mainly exhibit extracellular matrix loss and condylar cartilage degradation, is the most common chronic and degenerative maxillofacial osteoarthritis; however, no efficient therapy for TMJ-OA exists due to the poor understanding of its pathological progression. MicroRNA (miR)-140-5p is a novel non-coding microRNAs (miRNAs) that expressed in osteoarthritis specifically. To investigate the molecular mechanisms of miR-140-5p in TMJ-OA, primary mandibular condylar c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 44 publications
0
22
0
1
Order By: Relevance
“…To date, multiple targets of miR-140-5p have been identified as cartilage matrix modulators during the progression of OA from inflammation, chondrocyte hypertrophy and senescence to cartilage matrix degradation. miR-140-5p was found to inhibit inflammation by directly targeting Toll-like receptor (TLR)-4, C-X-C motif chemokine receptor (CXCR)-4, mothers against decapentaplegic homologue (SMAD) 3 [42], and interleukin-1 beta (IL-1β) [39]. Additionally, the inhibitory effect of miR-140-5p in chondrocyte hypertrophy has been shown through targeting histone deacetylase (HDAC)-4 [48] and SMAD1 [47].…”
Section: Mir-140 Targetsmentioning
confidence: 99%
“…To date, multiple targets of miR-140-5p have been identified as cartilage matrix modulators during the progression of OA from inflammation, chondrocyte hypertrophy and senescence to cartilage matrix degradation. miR-140-5p was found to inhibit inflammation by directly targeting Toll-like receptor (TLR)-4, C-X-C motif chemokine receptor (CXCR)-4, mothers against decapentaplegic homologue (SMAD) 3 [42], and interleukin-1 beta (IL-1β) [39]. Additionally, the inhibitory effect of miR-140-5p in chondrocyte hypertrophy has been shown through targeting histone deacetylase (HDAC)-4 [48] and SMAD1 [47].…”
Section: Mir-140 Targetsmentioning
confidence: 99%
“…Under the condition of diabetes, alterations in internal environmental factors, such as hyperglycaemia, hyperlipidaemia, hypertonic states, and microbial infection, cause changes in genetic information and affect the expression and regular activities of several miRNAs by intron transcription of host genes (Baker et al, 2017 ). The abnormal expression of miRNAs in serum and kidney tissues [such as let-7p, miR-140-5p (Li W. et al, 2019 ), miR-146a, miR-155-3p (Marques-Rocha et al, 2018 ), miR-29c, miR-31, miR-33a, and miR-451 (Graham et al, 2015 )] regulates the mRNA and protein expression of inflammatory cytokines by activating or inhibiting related signal transduction processes, causing the kidney to produce more of cytokines.…”
Section: Micrornas Cytokines and Dnmentioning
confidence: 99%
“…Whether and how the convergence of NF-κB and TGF-β signaling participate in inflammation-mediated hypertrophy of chondrocyte in OA was not clearly understood. Previous reports showed that IL-1β and TNFα could inhibit TGF-β-induced SMAD2/3 transcriptional activity 29 . And down-regulation of IL-1β and TNFα induced by LBP was accompanied by up-regulation of TGFβ1 30 .…”
Section: Discussionmentioning
confidence: 96%